KOPERASI SIMPAN PINJAM DAN MENINGKATKAN PENJUALAN ONLINE PADA KOPERASI SIMPAN PINJAM DI SURABAYA - RISTANTO, FELIX (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Creating a good relationship has a very beneficial for both parties. Good relationships can mask weaknesses and can achieve excess. Weaknesses in a good relationship is the time spent to set up the relationship. Observations were conducted at Cooperative saving and loan Surabaya has a purpose, to identify the concerns expressed in units of E-Kopwan and provide a solution to solve the problem. The problem is a poor relationship between Small and Medium businesses and cooperatives. A poor relationship between SMEs and cooperatives resulted online shopping has been closed by the cooperative. This observation is expected to solve the problems contained in the uni. Where the Small and Medium businesses as a distributor can establish good cooperation with the cooperative. In order to create benefits for both parties to make a online shopping.